PROBLEMATIKA BIMBINGAN DAN KONSELING BIDANG SPIRITUAL PESERTA DIDIK SMA: A SYSTEMATIC LITERATURE REVIEW (SLR) - Ma’rifatin Indah Kholili; Dinda Kamalia Mutiara Dewi; Kus Puji Santosa Edo Widiantaka; Rizqi Khanifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The purpose of this study was to find and describe various spiritual problems along with the completion of counseling guidance for high school students. The method used in this study was a Systematical Literature Review. The technique of collecting data is by collecting articles from several online journals. The author examines journal articles published between 2012-2020. The author found that there were 15 articles with 12 different problems. The results of this study show that various problems in the spiritual field include low religious tolerance, learning difficulties, high levels of anxiety, low levels of spiritual intelligence, lack of Islamic personality, low levels of interpersonal intelligence, low levels of religiosity, lack of noble morals, low self-esteem, bullying, juvenile delinquency, and smoking behavior that can be solved with Gestalt Prophetic (G-Pro) guidance and counseling, religiosity-based counseling guidance model, mind bubble meditation relaxation, integrative group counseling model, counseling guidance and spiritual intelligence, Islamic counseling approach, guidance theistic, group guidance, Al-Ghazali thought-based guidance and counseling, spirituality cognitive restructuring technique group counseling, Islamic intervention program model, Anwar Sutoyo's Islamic counseling guidance model, SEFT therapy (Spiritual Emotional Freedom Technique), ode mind map.